2021
DOI: 10.3390/ijerph18147682
|View full text |Cite
|
Sign up to set email alerts
|

Home Smoking Bans and Urinary NNAL Levels to Measure Tobacco Smoke Exposure in Chinese American Household Pairs

Abstract: Home smoking bans can reduce tobacco smoke exposure, but little is known about the impact for Chinese American household pairs. In this study of 202 household pairs with low acculturation, 53.9% reported a home smoking ban, 31.7% had inconsistent reports, and 14.4% reported no ban. With decreasing home smoking ban enforcement, more nonsmokers had tobacco smoke exposure (66.1%–86.2%) as measured by the tobacco-specific nitrosamine biomarker urine NNAL (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol). Despite rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Approximately 29.9% of them were children aged 3-11(14). Studies taken on the Asian-American community showed that approximately 38.3% of secondhand smoke exposure happened at home (15). This percentage is lower compared to some of the other ethnicities.…”
Section: Ethnicitiesmentioning
confidence: 94%
“…Approximately 29.9% of them were children aged 3-11(14). Studies taken on the Asian-American community showed that approximately 38.3% of secondhand smoke exposure happened at home (15). This percentage is lower compared to some of the other ethnicities.…”
Section: Ethnicitiesmentioning
confidence: 94%